Synthesis of Tin Oxide Nanoparticles (SnO2 NPs) and its Application in the Photocatalytic Degradation of Waste Alizarin DYE - Regmi, Shukra Raj; Khan, Nurul Hoda; Shawad, Narendra Prakash; Shahi, Dikpal Kumar; Joshi, Padam Raj; Chetry, Anup Basnet; Khatiwada, Lekha Nath; Baral, Ram Prasad; Adhikari, Rameshwar (Journal of Physical and Life Sciences, 2024)
The potential application of tin oxide nanoparticles in the photocatalytic degradation of toxic dyes has been investigated. In the present work, we have synthesized tin oxide nanoparticles by reducing tin chloride precursor, adding sodium borohydride under a controlled pH pathway. The synthesized nanoparticle was characterized by a UV-Visible Spectrophotometer, Fourier Transfer Infra-Red (FT-IR), Energy Dispersive X-ray (EDX), and X-ray Crystallography. On solving Debey-Scherrer’s equation, the average size of the particle is found to be 41.28 ± 14.59 nm with a crystallinity of 85.52%. The photocatalytic degradation is achieved by the average solar radiation of 5.64 ± 0.14 kWh/m2/day. The result reveals that complete degradation in light is obtained in 120 minutes, whereas in dark it is prolonged up to 300 minutes. The SnO2 NPs show 100% photocatalytic efficiency in the short time frame, but dark medium catalysis was limited to 68%. The photocatalytic degradation efficiency of SnO2 NPs is found to be superior to its catalytic degradation in the dark. The catalysis obeys pseudo-first-order kinetics with a high-rate constant. The mineralization process confirms the de-toxification of dye, which explores the application of SnO2 NPs as a potential catalyst. Our finding claims that tin oxide nanoparticles are efficient in solar-driven photocatalytic degradation of alizarin dye in a short period.